Midline survey: Transforming teacher education and learning - T-TEL (2017)

Annual Survey of Progress and Achievement - T-TEL (2019)

Transforming Teaching, Education & Learning Directors' Report 2022 - 2023 - T-TEL (Transforming Teacher Education and Learning, 2023)
T-TEL's 3rd Annual General Meeting (AGM) Report

OER Guidance for Colleges - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)

Theme 5: Teaching and Learning Materials (Professional Development Guide For Student Teachers) - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)

T-TEL's Terms, Messages and Communications Guide - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)

Open Educational Resources: Guidance for College of Education - T-TEL Professional Development Programme (Ministry of Education (Ghana), 2016)